1999
DOI: 10.1023/a:1018971313256
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: GL331's overriding drug resistance and higher cancer cell-killing activity suggest its superiority in clinical cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…On the other hand, through extensive structure-activity relationship studies, several potent and promising derivatives of PPT, such as NK-611(6), GL-331 (7), NPF (8), azatoxin (9), and TOP-53 (10), have also been obtained through numerous chemical modifications on the cyclolignan skeleton and reached phase I and phase II clinical trials as antitumor agents. For example, NK-611, a 2"-dimethylamino derivative of etoposide, was more potent than etoposide in DNA topoisomerase II (topo II) inhibition and cytotoxicity assays against a variety of human cancer lines [5,6]; GL-331 induced topo II dependent DNA cleavage and G-2 phase arrest, and was also shown to be active against many multidrug-resisitant cancer cell lines [7,8]; Azatoxin was designed using molecular modeling of the pharmacophore and was almost as potent as etoposide in inhibiting topo II [9,10]; TOP-53 exhibited more effective antitumor activity than etoposide against several types of cancer, especially lung metastatic tumors [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, through extensive structure-activity relationship studies, several potent and promising derivatives of PPT, such as NK-611(6), GL-331 (7), NPF (8), azatoxin (9), and TOP-53 (10), have also been obtained through numerous chemical modifications on the cyclolignan skeleton and reached phase I and phase II clinical trials as antitumor agents. For example, NK-611, a 2"-dimethylamino derivative of etoposide, was more potent than etoposide in DNA topoisomerase II (topo II) inhibition and cytotoxicity assays against a variety of human cancer lines [5,6]; GL-331 induced topo II dependent DNA cleavage and G-2 phase arrest, and was also shown to be active against many multidrug-resisitant cancer cell lines [7,8]; Azatoxin was designed using molecular modeling of the pharmacophore and was almost as potent as etoposide in inhibiting topo II [9,10]; TOP-53 exhibited more effective antitumor activity than etoposide against several types of cancer, especially lung metastatic tumors [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, NK-611, a 2"-dimethylamino derivative of etoposide, was more potent than etoposide in DNA topoisomerase II (topo II) inhibition and cytotoxicity assays against a variety of human cancer lines [5,6]; GL-331 induced topo II dependent DNA cleavage and G-2 phase arrest, and was also shown to be active against many multidrug-resisitant cancer cell lines [7,8]; Azatoxin was designed using molecular modeling of the pharmacophore and was almost as potent as etoposide in inhibiting topo II [9,10]; TOP-53 exhibited more effective antitumor activity than etoposide against several types of cancer, especially lung metastatic tumors [11,12]. cancer activity, the podophyllotoxin derivatives are used as antiviral agents in the treatment of herpes simplex type I and II, condyloma acuminatum caused by human papilloma virus (HPV) and other venereal and perianal warts [15][16][17][18][19], and also effective in the treatment of human immunodeficiency virus (HIV) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma is a leading cause of cancerrelated death worldwide, which is particularly high in East Asia [15]. Previous study showed that GL331 was more potent than its congener VP16 in killing hepatoma cells in vitro [2]. Therefore, this study further investigated the DDR triggered by GL331 in hepatoma HepG2 cells.…”
Section: Gl331 (mentioning
confidence: 96%
“…Though GL331 shares many physico-chemical and biochemical properties with its congener etoposide (VP16), it has the added advantage over VP16 to circumvent drug resistance attributed to MDR1 gene overexpression [2]. Several different mechanisms, including inhibition of protein tyrosine kinase, activation of protein tyrosine phosphatase, premature activation of Cdc2 kinase, and initiation of an inappropriate poly (ADP-ribose) polymerase activity, are suggested to account for the cytotoxicity induced by GL331 [3 -5].…”
Section: Gl331 (mentioning
confidence: 99%
“…Its two semisynthetic glucoconjugates, etoposide ( 2 ) and teniposide ( 3 ), are novel DNA topoisomerase II inhibitors marketed in several countries [6,7]. Some non-sugar substituted analogues, particularly N -linked congeners, exhibit superior pharmacological properties to etoposide, and consequently, several newer-generation clinical candidates, including NPF ( 4 ) [8], GL-331 ( 5 ) [9], and TOP-53 ( 6 ) [10], have emerged through C-4 modification as alternatives to overcome the drawbacks of etoposide. In addition, another important area of podophyllotoxin research involves the synthesis and design of novel spin-labeled PPT derivatives by our group over the past decades [1120], providing potential drugs with beneficial therapeutic profiles, e.g., improved activity or higher solubility, better pharmacokinetics, or reduced side effects.…”
Section: Introductionmentioning
confidence: 99%